Proces doskonalenia oceny równowagi budżetowej w Unii Gospodarczej i Walutowej - Giżyński, Juliusz; Wierzba, Ryszard (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
Fiscal discipline is one of fundamental requirements of the Economic and MonetaryUnion as specified in the provisions of the Maastricht Treaty (1992) and laterelaborated on in the Stability and Growth Pact (1997). EMU Member States fromthe beginning had serious difficulties in adhering to the fiscal rules, which ledto the first reform of the SGP in 2005 resulting in more flexible fiscal rules. Despitegood economic situation, EMU’s economies still had budget deficits which furtherincreased with the global financial crisis causing government debts to soar overacceptable limits. In due time, two further reforms of SGP were enacted, in 2011and 2013, introducing new indicators and improvements in the assessment of thegovernment budget balance in the euro area. Nevertheless, enforcement of newrules still will depend on EMU governments political will.